Iconographic Analysis on Intermediality Transfer of Undagi's Indigenous Knowledge Lexicon to Visual Cinematography - Noorwatha, I Kadek Dwi; Santosa, Imam; Adhitama, Gregorius Prasetyo; Remawa, Anak Agung Gede Rai (Universitas Negeri Semarang, 2025)
This study aims to investigate how the indigenous knowledge lexicon of Balinese undagi (traditional architects) in architecture can be transferred into visual cinematography to preserve cultural heritage, with a focus on engaging broader audiences. Employing an iconographic approach, the research analyzes the documentary Calaccitra Undagi Mahottama: Biografi I Gusti Made Gede (1843-1940) through three stages: pre-iconographic identification of visual motifs, iconographic interpretation of thematic meanings, and iconological assessment of cultural significance. Results reveal that Balinese architectural lexicons—such as Tri Mandala, Sanga Mandala, and CWSGR—are effectively abstracted into cinematic frames via intermediality, using symbolic natural imagery and spatial grids rather than physical structures to convey aesthetic and philosophical values. The study concludes that visual cinematography offers a potent medium for preserving architectural heritage by translating static spatial concepts into dynamic narratives, fostering continuity of traditional knowledge, particularly among younger generations, though its efficacy hinges on audience reception and contextual adaptation.